2011
DOI: 10.1503/cjs.038109
|View full text |Cite
|
Sign up to set email alerts
|

Mammoplasty for symmetry in breast reconstruction and histologic assessment

Abstract: Background:In breast reconstruction, complementary surgery on the contralateral breast is sometimes necessary to obtain a satisfactory aesthetic result. This complementary mammoplasty for symmetry gives the surgeon the opportunity to verify the state of the mammary glandular tissue to rule out a possible occult tumour in the contralateral breast. Our objective was to determine the prevalence of borderline lesions and of in situ and invasive carcinoma in specimens of the contralateral breast in a mammoplasty fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several studies have investigated the benefits of contralateral mammaplasty in large-breasted women both for obtaining symmetry and for histologic investigation of occult carcinoma. 24,25 The significant differences in patterns of contralateral symmetry procedure underscore its importance as a driving factor in terms of averaging out the extremes of breast size when it comes to choosing reconstructive options.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the benefits of contralateral mammaplasty in large-breasted women both for obtaining symmetry and for histologic investigation of occult carcinoma. 24,25 The significant differences in patterns of contralateral symmetry procedure underscore its importance as a driving factor in terms of averaging out the extremes of breast size when it comes to choosing reconstructive options.…”
Section: Discussionmentioning
confidence: 99%
“…Our incidence of ADH is slightly higher compared with previous reports. However, Horo et al assessed 145 reduction mammoplasties and reported borderline lesions (ADH) in 12 (15.6%) of the patients (15).…”
Section: Discussionmentioning
confidence: 99%